Selective and tunable H2 adsorption/sensing performance of W-doped graphene under external electric fields: A DFT study. (8th August 2022) - Yang, Shulin; Xie, Shunlin; Tan, Lun; Lei, Gui; Xu, Huoxi; Lan, Zhigao; Wang, Zhao; Gu, Haoshuang
Abstract: W-doped graphene and its selective gas adsorption/sensing performance are studied through first-principles density functional theory (DFT) calculations. A single W atom is stably anchored into the graphene plane with a high binding energy of −9.325 eV. The W-doped graphene interacts more strongly with H2 compared to NH3, CH4, CO, SO2 or H2 S. The H2 adsorption system also has a higher adsorption energy of −1.035 eV. Furthermore, the W-doped graphene exhibits the highest sensor response to H2 with the largest number of transferred charges and the biggest change in the band gap. A negative electric field improves the interaction between the H2 and the W-doped graphene by increasing the adsorption energy and promoting charge transfer. However, the adsorption of the H2 is significantly weakened upon the application of a positive electric field; the adsorbed H2 is easily desorbed from the W-doped graphene with a modulated recovery time as short as ∼4.099 s at room temperature (300 K) upon a +0.4 V Å −1 increase in the electric field. These results reveal that the W-doped graphene has promising selective and tunable H2 adsorption/sensing performance upon the application of external electric fields. Highlights: W atom is stably doped into graphene (G) with high binding energy of −9.325 eV. H2 interacts strongly with W-doped G (W-G) with elongated H–H of 2.044 Å. W-G exhibits a higher sensor response to H2 than NH3, CH4, CO, SO2 or H2 S. Tunable adsorption of H2 on W-G can be realized with external electric fields. W-G can show outstanding selective and tunable H2 adsorption/sensing property.